Clavicular osteotomy approach for difficult shoulder surgery - Khalid, Kamarul Ariffin; Mah, Edward T (2008)
The deltopectoral surgical approach has long been the workhorse for the anterior approach to the shoulder joint. It was described early in the last century by Thompson (1918) and Henry (1927). Although this approach can be used for many surgical procedures, one of its drawbacks is difficulty in exposing and visualizing the glenoid. It also gives limited access to the greater tuberosity and rotator cuff.